Chaos engineering in cloud platforms - Vered Sheinman (EPJ Web of Conferences)
This article explores the implementation and impact of chaos engineering (CE) on cloud platforms, emphasizing its role in enhancing system resilience and reliability. Various CE methodologies, such as fault injection and passive observation, are discussed, alongside case studies from major cloud service providers (AWS, Azure, GCP). The integration of artificial intelligence and machine learning in automating and refining chaos experiments is analyzed, highlighting its growing importance as cloud infrastructures become more complex. The potential of CE for proactive prediction and management of system vulnerabilities is underscored, illustrating its capability to preemptively identify and address weaknesses. Through a comprehensive review of existing research and practical case studies, this article aims to demonstrate how CE can effectively bolster cloud platform resilience. The market for CE tools, valued at two billion dollars in 2022, is projected to grow significantly, driven by increasing investment and the need for robust security models. The historical development of CE, from Netflix's Chaos Monkey to contemporary practices, is also covered, showcasing the evolution of CE and its adoption by tech giants to maintain system robustness and reliability.